2022
DOI: 10.7717/peerj.13681
|View full text |Cite
|
Sign up to set email alerts
|

A complete season with attendance restrictions confirms the relevant contribution of spectators to home advantage and referee bias in association football

Abstract: Background Due to the unfortunate pandemic situation, the phenomena of home advantage and referee bias in sports have recently received a particular research attention, especially in association football. In this regard, several studies were conducted on the last portion of the 2019–20 season: the majority of them suggests a reduction—but not the elimination—of the two phenomena, with some exceptions in which no reduction was found or, at the other extreme, the phenomena were not observed at all. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…In addition, comparing spectator and ghost play seasons, HA scores were higher for spectator seasons (59.4%) than for ghost play seasons (57.0%). This result is like findings from Sors et al (2022a) (58.5% with spectator vs. 54.75% without spectators) and Dellagrana et al (2023) (66.6% with spectator vs. 57.2% without spectators).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, comparing spectator and ghost play seasons, HA scores were higher for spectator seasons (59.4%) than for ghost play seasons (57.0%). This result is like findings from Sors et al (2022a) (58.5% with spectator vs. 54.75% without spectators) and Dellagrana et al (2023) (66.6% with spectator vs. 57.2% without spectators).…”
Section: Discussionsupporting
confidence: 87%
“…While some studies showed that the HA did not completely disappear in empty stadiums (Wunderlich et al, 2021), other research on the influence of absolute spectator numbers (Moore and Brylinsky, 1993), stadium occupancy (Agnew and Carron, 1994), or noise levels (Salminen, 1993) have shown that spectators do not directly (or only to a very limited extent) take effect on the HA. More recently, studies showed that in certain leagues, the HA totally disappeared in home games without spectators (Fischer and Haucap, 2020), while others presented a lesser HA magnitude (Sors et al, 2022). However, when considering the basketball game, the crowd support seems to have an important effect on team performance.…”
Section: Impact Of Home Advantage On Match Performancementioning
confidence: 99%
“…Admittedly, this has provided the opportunity to examine whether fans are an important influence on the HA of football matches. An analysis of all “ghost matches” in the 2020-21 season in the top five national leagues of UEFA’s first and second divisions found that HA was significantly reduced in the absence of spectators compared to the season with spectators, while the absence of significant differences in referee bias was considered to be related to the absence of spectators (Sors et al, 2022a). Also using the “ghost matches” during the epidemic as material, Leitner et al (2022) conducted a systematic literature review of the importance of football fans based on 21 empirical studies, showing that HA declined during empty games, mainly due to a reduction in referee bias and a lack of emotional support for teams, thus validating the importance of fans for team success.…”
Section: Crowd Size and Home Field Advantagementioning
confidence: 99%